Economic viability of different surveillance strategies for the control of paratuberculosis in Swiss dairy cattle - Silja Griss; Gertraud Schüpbach-Regula; Luís P. Carmo; Mireille Meylan; Beat Thomann (Preventive Veterinary Medicine, 2025)

A half-century of demographic changes in a green turtle (Chelonia mydas) foraging aggregation during an era of seagrass decline - P. A. Meylan; R. F. Hardy; J. A. Gray; A. B. Meylan (Marine Biology, 2022)
To understand the demographic responses of green turtles to seagrass decline, we examined a data set from study of a mixed-stock foraging aggregation of immature green turtles, Chelonia mydas, collected in Bermuda (32 o 18’N, − 64 o 46’W) over five decades. Average turtle size (SCL min ) and mass declined by 22.3% and 58.2%, respectively. Aggregation size structure shifted to smaller sizes and now consists of more small turtles and fewer large turtles. Density (turtles ha −1 ) increased significantly but biomass (kg ha −1 ) remained unchanged and low compared to C. mydas biomass observed elsewhere. Green turtles exhibited reduced site fidelity during two portions of the study period, suggesting increased foraging effort. Reduction in turtle body condition index and seagrass coverage occurred from offshore to inshore. Changes in aggregation composition and behavior were consistent with expectations given a documented decline in seagrass availability, combined with increased output from source rookeries. Apparent response to resource decline is traced back to 1976, well before seagrass loss was first documented. Green turtles and their primary food source ( Thalassia testudinum ) are at the northern limit of their range in Bermuda, where seagrasses would be expected to have a reduced tolerance for natural grazing pressure and increased susceptibility to synergistic stressors, especially temperature, bioturbation and phosphorus limitation. Our results suggest that synergistic stressors, and not green turtles alone, have produced the observed reduction in seagrasses on the Bermuda Platform. Given that seagrass declines have been reported worldwide, our findings may suggest how green turtles will respond elsewhere.

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

CSF lactate for accurate diagnosis of community-acquired bacterial meningitis - S. Giulieri; C. Chapuis-Taillard; K. Jaton; A. Cometta; C. Chuard; O. Hugli; R. Du Pasquier; J. Bille; P. Meylan; O. Manuel; O. Marchetti (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Turtle groups or turtle soup: dispersal patterns of hawksbill turtles in the Caribbean - J. M. BLUMENTHAL; F. A. ABREU‐GROBOIS; T. J. AUSTIN; A. C. BRODERICK; M. W. BRUFORD; M. S. COYNE; G. EBANKS‐PETRIE; A. FORMIA; P. A. MEYLAN; A. B. MEYLAN; B. J. GODLEY (Molecular Ecology, 2009)
Despite intense interest in conservation of marine turtles, spatial ecology during the oceanic juvenile phase remains relatively unknown. Here, we used mixed stock analysis and examination of oceanic drift to elucidate movements of hawksbill turtles ( Eretmochelys imbricata ) and address management implications within the Caribbean. Among samples collected from 92 neritic juvenile hawksbills in the Cayman Islands we detected 11 mtDNA control region haplotypes. To estimate contributions to the aggregation, we performed ‘many‐to‐many’ mixed stock analysis, incorporating published hawksbill genetic and population data. The Cayman Islands aggregation represents a diverse mixed stock: potentially contributing source rookeries spanned the Caribbean basin, delineating a scale of recruitment of 200–2500 km. As hawksbills undergo an extended phase of oceanic dispersal, ocean currents may drive patterns of genetic diversity observed on foraging aggregations. Therefore, using high‐resolution Aviso ocean current data, we modelled movement of particles representing passively drifting oceanic juvenile hawksbills. Putative distribution patterns varied markedly by origin: particles from many rookeries were broadly distributed across the region, while others would appear to become entrained in local gyres. Overall, we detected a significant correlation between genetic profiles of foraging aggregations and patterns of particle distribution produced by a hatchling drift model (Mantel test, r = 0.77, P r = 0.83, P